The handbook of global health policy - Brown, Garrett Wallace; Yamey, Gavin; Wamala, Sarah P. (Chichester, West Sussex ; Malden, MA : Wiley Blackwell., 2014)
"The Handbook of Global Health Policy provides a definitive source of the key areas in the field. It examines the ethical and practical dimensions of new and current policy models and their effect on the future development of global health and policy. Maps out key debates and policy structures involved in all areas of global health policy Isolates and examines new policy initiatives in global health policy Provides an examination of these initiatives that captures both the ethical/critical as well as practical/empirical dimensions involved with global health policy, global health policy formation and its implications Confronts the theoretical and practical questions of 'who gets what and why' and 'how, when and where?' Captures the views of a wide array of scholars and practitioners, including from low- and middle-income countries, to ensure an inclusive view of current policy debates "--
"Provides a state-of-the-art guide to global health and its associated policies, mapping out key debates, new initiatives, and policy structure"--
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: World health; Public health -- International cooperation; Globalization -- Health aspects; POLITICAL SCIENCE -- Public Policy -- General; Globalization -- Health aspects; Public health -- International cooperation; World health; Electronic books